Breast and cervical cancer mortality in the western Amazon: A time series study between 1980 and 2014. Issue 21 (28th May 2021) - Leitão, Francisco Naildo Cardoso; Bezerra, Italla Maria Pinheiro; de Lima, Marcos Vinicius Malveira; Pimentel, Renata Macedo Martins; Jr, Hugo Macedo; Morais, Mauro José de Deus; Machado, Ana Paula Araújo; Abreu, Luiz Carlos de
Abstract : Abstract: Among the main types of neoplasms in the female population, breast and cervical cancers are the most important due to their high morbidity and mortality rates. The mortality has been proportionally higher in developing countries. Analysis of the trend of cancer mortality in Brazil revealed a considerable difference in the pattern of deaths between the regions. To analyze the trend of mortality due to breast and cervical cancers in women. Retrospective study of a series of death cases, using secondary data from the mortality information system (SIM) of the Ministry of Health. The deaths were identified as the underlying cause of breast and cervical cancers, including malignant neoplasms of the uterus without other specifications, occurring from 1980 to 2014. Thus, the annual standardized age-specific mortality rates by the world population were applied. For trend analysis, regression models were utilized in which the mortality rates were considered dependent variables and years the independent variable. Polynomial regression models and a Prais–Winsten regression model were adopted. Cervical cancer presented a mortality rate ranging from 2.15 to 10.69 per 100, 000 women from 1980 to 2014, with a tendency for stability. Breast cancer mortality rate varied from 3.81 to 11.47 per 100, 000 women from 1981 to 2014, indicating a growing trend. There is a significant increase in the mortality rate for breast cancer and stability of cervical cancers in the State of Acre from 1980 to 2014, evidencing a concern in their care and monitoring. Above all, guaranteed access, especially to the population of women at social risk, and the search for effective screening should be emphasized in the formation of the care line and the Health Care Network in the State of Acre.